Public Feminisms From Academy to Community - Baker, Carrie; Dove-Viebahn, Aviva (Lever Press, 2023)
The field of feminist studies grew from the U.S. women's movements of the 1960s and 1970s and has continued to be deeply connected to ongoing movements for social justice. As educational institutions are increasingly seeing public scholarship and community engagement as relevant and fruitful complements to traditional academic work, feminist scholars have much to offer in demonstrating different ways to inform and interact with various communities. In Public Feminisms: From Academy to Community edited by Carrie N. Baker and Aviva Dove-Viebahn, a diverse range of feminist scholar-activists write about the dynamic and varied methods they use to reach beyond the traditional academic classroom and scholarly journals to share their work with the public. Part one explores how feminist scholars engage broader audiences through art, media, and public programming, including essays on a public discussion series teaching intersectional feminist analysis of popular films, and a podcast from Latina scholars discussing issues of reproductive justice, social justice, motherhood, sexuality, race, and gender. Part two focuses on activism and public education, including essays on "Take Back the Night," and archiving the women's march protests. Part three turns to public writing and scholarship, including an essay on elevating the perspectives and voices of underrepresented creatives in the film and television industry. Part four explores feminist pedagogies for community engagement and for teaching public feminisms. Accessible and engaging to a broad range of readers, the essays in this volume are a rich resource for scholars and students interested in infusing their academic knowledge into the public sphere. With this timely book, the editors offer an opportunity to reflect on the meaning and importance of community engagement and highlight some of the important public-facing work feminist scholars are doing today. Faculty, graduate, and undergraduate students, as well as administrators hoping to increase their schools' connections to the community, will find this volume indispensable.